Value of Specialist Pathology Review in a Single Statewide Gynecologic Cancer Service. Issue 1 (1st January 2016) - Melon, Jerome; Leung, Yee; Salfinger, Stuart G.; Tan, Jason; Mohan, Ganendra; Cohen, Paul A.
Abstract : Objective: A case review by specialist diagnostic pathologists as part of a Gynecologic Oncology Multi-disciplinary Tumor group has the potential to influence the management of patients with cancer. The primary aim of this study was to determine the frequency of diagnostic discrepancies between the initial (nonspecialist) and final pathological diagnoses in cases referred to the Gynecologic Oncology Tumor Conference (TC) in Western Australia and the impact of such revised diagnosis on clinical management. A secondary aim was to assess the evolving workload encountered by the TC during a 5-year interval. Methods: The records of the weekly TC for the 2 calendar years 2008 and 2013 were examined, and histological and cytological specimens that had been initially assessed by "outside" (nonspecialist) pathology departments, and subsequently reviewed by specialist pathologists, were assessed. The initial and final diagnoses were compared, and where the pathological findings were amended upon review, it was determined whether the change affected clinical management. Diagnostic discrepancies that resulted in a change in patient management were classified as major, whereas discrepancies that did not affect patient management were classified as minor. Results: A total of 481 outside cases were included among 2387 cases presented for histological review at the TC during the 2 years. For outside cases alone, the incidence of major diagnostic discrepancies was 3.4% in 2008, 5.5% in 2013 (no significant difference, P = 0.3787), and 4.6% for the 2 years combined. A recommendation for surgery was the most common change in clinical management as a result of major discrepancy. The minor discrepancy rate was 4.4% of outside cases for both years combined. Pathological discrepancies (major and minor) of the uterine corpus and cervix were most frequent, followed by those of the vulva and ovary. There was a 48.4% increase in total case discussions at the TC during the interval period with a significant rise in nonmalignant cases, 29.8% of the total cases in 2008 compared with 36.8% in 2013 ( P = 0.0004). Conclusions: Nonspecialist pathology departments maintained a high level of reporting accuracy during the interval period, with the major discrepancy rate not changing significantly between 2008 and 2013. Specimens from the uterine corpus and cervix in particular may prove diagnostically challenging on occasion. A pathology review of outside cases by a tertiary-based laboratory in conjunction with a TC can identify a small but clinically significant number of cases that lead to a change in clinical management. It is uncertain whether this affects patient outcomes.